Crystal structure of isovalent substituted layered indates Ba1−xSrxLa2In2O7 - Titov, Yu. A.; Belyavina, N. M.; Slobodyanik, M. S.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
Conditions of isovalent substitution of barium atoms in layered perovskite-like structure (LPS) of BaLa2In2O7 by the type Ba1−xSrxLa2In2O7 (0 ≤ x ≤ 0.75) are determined. The LPS of indates Ba1−xSrxLa2In2O7 (x = 0.2, 0.5, and 0.7) are determined by X-ray powder diffraction. It is found that the LPS of Ba1−xSrxLa2In2O7 belongs to the SrLn2Sc2O7-type structure (sp. gr. Fmmm), and the interrelations composition — constitution of LPS are determined. It is shown that the increase of the strontium content in LPS Ba1−xSrxLa2In2O7 increases a degree of deformation of interblock polyhedra AO9 and decreases the length of the interblock distance A(2)−O(2) in LPS Ba1−xSrxLa2In2O7.